New bands in ¹⁹²Tl using gamma spectroscopy techniques - Easton, Jayson Lee (University of the Western Cape, 2017)
>Magister Scientiae - MSc === High spin excited stats in¹⁹²Tl were studied using gamma-ray spectroscopy. The study included taking an active part in performing the experiment, understanding the experimental procedure, electronics and data acquisition in this experiment. The high spin states in ¹⁹²Tl were produced using a ³⁷Cl beam and ¹⁶⁰Gd target. The nine clovers of the AFRODITE array were placed at 90° and 135°. The target was thin, allowing the residual thallium nuclei to recoil in vacuum. Two weeks of data was acquired and analysed in this work. In addition more data was acquired in order to perform DSAM lifetime measurements, but this is beyond the scope of this work. The preliminary data analysis of the thin target data involved energy and time-gain matching calibrations as well as Doppler shift and gain drift corrections. Then the data were sorted into matrices and spectra for the actual analysis. The known level scheme of ¹⁹²Tl was extended by more than 50 new transitions placed in three new bands. A chiral partner to the yrast band in ¹⁹²92Tl was searched for but not found. But there is still a possibility such a band to be discovered, when the additional three weekends of data (including the DSAM lifetime measurements) undergo such an analysis.